Epistemological beliefs of students of Pedagogy: validation of the questionnaire and analysis of differences - Cuéllar Fajardo, Mayra (2017)
This study describes epistemological beliefs from students in the Degree of Pedagogy at the University of Barcelona (Spain), and analyzes differences inthese beliefs according to their year of study, gender, and age. To do so, the psychometric properties (construct validity and internal consistency) of SchommerEpistemological Questionnaire (1990) were estimated. 229 students participated.Results show that the reliability of the instrument is moderate (a = .653), and the factorial structure revealed validates the epistemological model proposed by Schommer. Furthermore, the results indicate that final year student beliefs aremore sophisticated than first year student beliefs in respect to learning ability andto the structure and certainty of knowledge. Differences were also found owningto the student’s gender, but not to age.